Two new species of Macropsini (Hemiptera: Auchenorrhyncha: Cicadellidae: Eurymelinae) from the highlands of New Guinea - Tishechkin, Dmitri Yu. (Zootaxa, 2026)
Illustrated descriptions of two new species of Macropsini from the highlands of New Guinea, Pediopsis vikhrevi sp. nov. and Macropsella habbema sp. nov., are provided. Pediopsis vikhrevi sp. nov. differs from all other known species of Pediopsis by the shape of the dorsal connective processes and the aedeagus. M. habbema sp. nov. has peculiar bifurcated pygofer appendages, differing in this character from other Australian and New Guinean Macropsini.